Association of troponin-defined myocardial injury with adverse long-term survival among patients with chronic kidney disease - Fei Ma; Enhong Han; Jianjun Gao (PLoS ONE, 2026)
Objective Chronic kidney disease (CKD) is associated with increased mortality, however, the impact of troponin-defined myocardial injury within this population remains poorly understood. This study aimed to investigate the associations between troponin-defined myocardial injury and long-term mortality in CKD patients. Methods This observational study analyzed 22,772,953 weighted records of adult CKD patients from National Health and Nutrition Examination Survey (1999–2004) databases. Myocardial injury was defined by at least one elevated high-sensitivity troponin (hs-cTn) assay, present in 26.6% of the cohort. Cox regression models adjusted for baseline characteristics and comorbidities were used to assess the associations between troponin-defined myocardial injury and all-cause and cardiovascular mortality. Sensitivity analyses excluding patients with known cardiovascular disease (CVD) were performed to evaluate the robustness of the findings. Results Patients with troponin-defined myocardial injury were older and had a higher prevalence of CVD, hypertension, diabetes, as well as a lower estimated glomerular filtration rate (eGFR), compared with those without troponin-defined myocardial injury. Over a median follow-up of 11.6 years, survival was significantly worse among patients with troponin-defined myocardial injury at 1, 5, 10, and 15 years. The adjusted hazard ratios (aHR) for all-cause mortality and cardiovascular mortality in patients with troponin-defined myocardial injury were 1.81 (95% CI 1.51–2.17) and 2.03 (95% CI 1.47–2.79), respectively. Sensitivity analysis excluding records with pre-existing CVD showed similar trends, with an aHR of 1.86 (95% CI 1.56–2.21) for all-cause mortality and 2.44 (95% CI 1.83–3.24) for cardiovascular mortality. Conclusion As a marker for troponin-defined myocardial injury, hs-cTns were independently associated with worse long-term survival among CKD patients. However, the observational design precludes causal inference, and single time-point troponin measurements limit the assessment of dynamic changes in myocardial injury.